Development of Project-Based Learning Guide on Pollution and Environmental Conservation Material at SMA 1 Jekulo Kudus (Journal of Innovative Science Education, 2018)
One of the efforts to be an Adiwiyata school is done by improvement of knowledge, activities, attitudes, and skills of students regarding environment. The activities, attitudes, and skills, and the cognitive learning outcome of students were still low. Project learning is considered as one of the approaches to create learning environment that can support students to build knowledge, attitudes, and skills. The study aimed to describe the characteristics of learning guide and to test the validity, practicality, and effectiveness of learning guide on pollution and environmental conservation material. The study implemented research and development (R&D) design. The learning media was validated by the validator. The practicality was determined by student and teacher response. The effectiveness was observed from the activities, attitudes, and skills, and the cognitive learning outcome. The activities, attitudes, and skills were analyzed using percentage descriptive. The cognitive learning outcome was tested using independent t-test. The result of the study showed that the learning guide on pollution and environmental conservation material was valid, practical, and effective. The learning guide was declared valid with good category. The learning guide was declared stated practical by getting positive response from the students, and the teachers gave very good response. The learning guide was declaredeffective with activities, attitudes, and skills in very good category. The classical completeness of experiment class reached the Minimum Mastery Criteria 83,3% and control class 45,2%. There was significant difference between the post-test average score of experiment class and control class.